2011
DOI: 10.1007/s12038-011-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of the 93D puff of Drosophila melanogaster

Abstract: The 93D puff of Drosophila melanogaster became attractive in 1970 because of its singular inducibility by benzamide and has since then remained a major point of focus in my laboratory. Studies on this locus in my and several other laboratories during the past four decades have revealed that (i) this locus is developmentally active, (ii) it is a member of the heat shock gene family but selectively inducible by amides, (iii) the 93D or heat shock RNA omega (hsr row) gene produces multiple nuclear and cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 119 publications
(154 reference statements)
0
84
0
Order By: Relevance
“…A major function of the nuclear hsrω transcripts is to organize the nucleoplasmic omega speckles which primarily regulate the functional availability of hnRNPs and some other key RNA-processing proteins (Lakhotia et al 1999;Prasanth et al 2000;Jolly and Lakhotia 2006;Lakhotia 2011). In view of such fundamental role, it is not surprising that majority of the embryos that have little or subthreshold levels of these transcripts because of the null allele (present results) or global RNAi ) die before hatching.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A major function of the nuclear hsrω transcripts is to organize the nucleoplasmic omega speckles which primarily regulate the functional availability of hnRNPs and some other key RNA-processing proteins (Lakhotia et al 1999;Prasanth et al 2000;Jolly and Lakhotia 2006;Lakhotia 2011). In view of such fundamental role, it is not surprising that majority of the embryos that have little or subthreshold levels of these transcripts because of the null allele (present results) or global RNAi ) die before hatching.…”
Section: Discussionmentioning
confidence: 58%
“…The hsrω gene produces multiple noncoding transcripts (Garbe et al 1986), of which the large (>10 kb) nucleus-limited hsrω-n transcripts organize the nucleoplasmic omega speckles (Prasanth et al 2000;Mallik and Lakhotia 2011), which sequester the various hnRNPs and certain other RNAprocessing proteins that are not actively engaged at a given time (Lakhotia et al 1999;Prasanth et al 2000;Jolly and Lakhotia 2006). Our recent studies (Mallik and Lakhotia 2009a, b, 2010, 2011Onorati et al 2011) have revealed that the hsrω RNA also affects, directly or indirectly, activities of DIAP1, CBP, JNK pathway, proteasome, ISWI, lamin C, etc., highlighting roles of these noncoding RNAs in multiple cellular networks (Lakhotia 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined the possibility that these two formulations, especially the mercury based RS, may cause a mild/chronic stress which may result in improved tolerance to a more severe subsequent stress. Several studies in Drosophila have shown that heat shock brings about a rapid and dramatic change in the distribution of nucleoplasmic and chromosome associated hnRNPs so that soon after heat shock, almost all of them get aggregated at the 93D or hsrω locus [23], [27], [28], [50]. Our present observation on the in situ distribution of three different hnRNPs, viz., Hrp36, Hrp38 and Hrp40, do not provide any evidence for the AR- or RS-fed larval cells being under stress since in all cases, the nuclear distribution of the three hnRNPs was qualitatively similar to that seen in normally fed larval cells.…”
Section: Discussionmentioning
confidence: 65%
“…In Drosophila, the activity of the ISWI ATPase was recently found to be regulated by hsrω, a class of functionally conserved developmentally regulated long ncRNA responsible for the assembly and organization of the hnRNP-containing omega speckles (Onorati et al 2011). Omega speckles are specialized nuclear compartments localized in the nucleoplasm close to chromatin edges, containing diverse hnRNPs (Lakhotia 2011). The nucleoplasmic omega speckles play essential roles in storage and sequestration of hnRNP family members and other proteins involved in RNA processing and maturation in normal as well as stressed cells.…”
Section: Rnamentioning
confidence: 99%